More than one million barriers fragment Europe’s rivers - Josh Jones (Nature, 2020)
Rivers support some of Earth’s richest biodiversity and provide essential ecosystemservices to society, but they are often fragmented by barriers to free flow. In Europe,attempts to quantify river connectivity have been hampered by the absence of aharmonized barrier database. Here we show that there are at least 1.2 million instreambarriers in 36 European countries (with a mean density of 0.74 barriers per kilometre),68 per cent of which are structures less than two metres in height that are oftenoverlooked. Standardized walkover surveys along 2,715 kilometres of stream lengthfor 147 rivers indicate that existing records underestimate barrier numbers by about61 per cent. The highest barrier densities occur in the heavily modified rivers ofcentral Europe and the lowest barrier densities occur in the most remote, sparselypopulated alpine areas. Across Europe, the main predictors of barrier density areagricultural pressure, density of river-road crossings, extent of surface water andelevation. Relatively unfragmented rivers are still found in the Balkans, the Balticstates and parts of Scandinavia and southern Europe, but these require urgentprotection from proposed dam developments. Our findings could inform theimplementation of the EU Biodiversity Strategy, which aims to reconnect 25,000kilometres of Europe’s rivers by 2030, but achieving this will require a paradigm shiftin river restoration that recognizes the widespread impacts caused by small barriers.